Challenges of Gender Stereotypes in Women's International Leadership Careers: Literature Review - Bayu Suryo Putro; Didin Hikmah Perkasa; Ahmad Badawi Saluy (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This literature review examines the challenges that gender stereotypes pose to women's advancement in international leadership roles. The review identifies obstacles such as limited access to top positions, gender pay gaps, and societal attitudes that favor men. Gender stereotypes contribute to conscious and unconscious biases, discriminatory practices, unequal opportunities, and the "double bind" phenomenon, where women must balance competence and likability. These challenges are exacerbated in international contexts by cultural differences and varying societal norms. The review concludes that gender stereotypes significantly hinder women's progress in international leadership, necessitating organizational efforts to dismantle biases, ensure equal access to opportunities, and foster inclusive cultures. Further research is recommended to explore the intersectional impact of gender stereotypes in international settings.